Bean dreg nanocellulose probiotic microcapsule as well as preparation method and application thereof
By extracting and preparing the nanocellulose of bean dregs combined with peanut protein and jenipine, a composite product is formed as a microcapsule wall material and embedding Lactobacillus plantarum, the problem of low utilization of insoluble fibers in bean dregs is solved, and the high-value utilization of bean dregs by-products and the healthy effects of probiotic microcapsules are achieved.
Patent Information
- Application Number
- CN202510221471.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-04-11
AI Technical Summary
How to improve the utilization rate of insoluble fibers in soybean dregs, and use the by-products of soy products in the production of soy products to achieve high-value utilization of by-products in food production.
By extracting and preparing bean dregs nanocellulose, and combining with peanut protein and genipin, a composite product is formed as a microcapsule wall material, embedding Lactobacillus plantarum, and probiotic microcapsules are prepared.
The high-value utilization of by-products of bean dregs is achieved, the health benefits of the products are improved, and the intestinal delivery and biological activity protection of Lactobacillus plantarum is ensured.
Smart Images

Figure CN119791288A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of probiotic microcapsule food processing, and in particular to dregs nanocellulose probiotic microcapsules, a preparation method and application thereof. Background Art
[0002] Okara is the yellow-white insoluble component of soybeans that remains in the filter bag during the production of soy products such as soy milk and tofu. It has a water content of 70%-80%, so it is easy to spoil and difficult to preserve. Okara contains a large amount of nutrients with high biological value, such as protein (11-43%), total dietary fiber (TDF) (13-63%), lipids (5-25%) and isoflavones (IFs) (0.5-1 mg / g). A large number of studies have shown that most of the fiber in okara is insoluble dietary fiber, which has an adverse effect on the taste and texture of food. After defatting, removing protein, and extracting low molecular weight carbohydrates from okara with ethanol, okara cell walls with a yield of 77.2% can be obtained. By stirring or standing extraction with different concentrations of CDTA+NH4 oxalate, NaOH, KOH, and NaClO2 / acetic acid, fractions S1-5 and cellulose-rich residues can be obtained, respectively, of which the residual amount of insoluble fiber is about 21.9%. The insoluble fiber in dregs plays a beneficial role in many physiological processes and in the prevention of some diseases, such as reducing the risk of colon cancer, antibacterial, anti-tumor, and improving immunity. In the in vitro digestion simulation experiment, the structure, physicochemical properties, adsorption properties, and potential biological activity of dregs cellulose have different performances at different stages. Dregs cellulose can be used to produce functional foods and even for the adjuvant treatment of some diseases. The ideal adsorption, physicochemical properties, slight antioxidant activity, and potential biological activity also indicate the application potential of dregs cellulose in food processing. Therefore, how to improve the utilization rate of insoluble fiber in dregs is an urgent problem to be solved.
[0003] Microencapsulation refers to the technology of encapsulating solids, liquids or gases in tiny and sealed capsules so that they are released at a controlled rate only under specific conditions. It is widely used in the food and pharmaceutical industries to improve the chemical stability of bioactive compounds, protect them from deteriorating adverse environmental conditions (such as light, moisture and oxygen), control the targeted release of bioactive compounds, and obtain better treatment of bioactive compounds. The complex of wall materials is mainly used for proteins and polysaccharides, and protein-polysaccharide complexes have better effects than single wall materials due to their higher chemical protection and stability.
[0004] Make full use of dregs, a by-product of soy product production, extract its insoluble fiber and prepare nanocellulose, then prepare the composite product of dregs nanocellulose and peanut protein and use it as microcapsule wall material, use plant lactobacillus as core material to prepare probiotic microcapsules, form a production technology system for probiotic microcapsules using dregs insoluble fiber and peanut protein as raw materials, promote the development and utilization of resources, and provide an important basis for improving the utilization rate of food waste and the preparation of probiotic microcapsules. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a bean dregs nanocellulose probiotic microcapsule, a preparation method and an application thereof, aiming to prepare bean dregs nanocellulose by extraction and prepare a composite product of bean dregs nanocellulose and peanut protein, which can not only realize the in vivo delivery of Lactobacillus plantarum, but also apply the insoluble polysaccharides of plants as wall materials in the preparation of microcapsules, so as to realize the utilization of bean dregs, a by-product in the production of soy products, not only turning waste into treasure and realizing the high-value utilization of by-products in food production, but also improving the health effects of the products.
[0006] To achieve the above object, the present invention is achieved through the following technical solutions:
[0007] A soybean dregs nanocellulose probiotic microcapsule comprises probiotics as a core material and a wall material for embedding the core material; the wall material comprises soybean dregs nanocellulose, peanut protein and genipin, and the probiotics are plant lactobacillus.
[0008] Preferably, the above-mentioned okara nanocellulose probiotic microcapsule is prepared from the following raw materials in the above-mentioned parts by weight: 98-102 parts of okara nanocellulose, 98-102 parts of peanut protein, 0.8-1.2 parts of genipin, and 2 parts of Lactobacillus plantarum.
[0009] Preferably, the above-mentioned okara nanocellulose probiotic microcapsule is prepared from the following raw materials in the above-mentioned parts by weight: 100 parts of okara nanocellulose, 100 parts of peanut protein, 1 part of genipin, and 2 parts of Lactobacillus plantarum.
[0010] Preferably, the above-mentioned soybean dregs nanocellulose is obtained by physically modifying the original cellulose extracted from soybean dregs; the peanut protein is food-grade peanut protein; genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and Lactobacillus plantarum is a live bacterium after activation and expansion.
[0011] A method for preparing soybean dregs nanocellulose probiotic microcapsules, the steps of which are as follows:
[0012] Step 1: Extraction of okara cellulose: Fresh okara is dried, defatted, deproteinized, water-soluble polysaccharides are removed, dialyzed and purified, and then recovered and freeze-dried to obtain okara cellulose;
[0013] Step 2: Preparation of okara nanocellulose: treating the okara raw cellulose with ultrasound and homogenization to obtain physically modified okara nanocellulose;
[0014] Step 3: Preparation of a composite product of okara nanocellulose and peanut protein: 98-102 parts by weight of okara nanocellulose and 98-102 parts by weight of Zhonglian peanut protein are used to prepare a composite product with 0.8-1.2 parts by weight of genipin as a cross-linking agent to obtain a wall material for embedding probiotics;
[0015] Step 4: Activation and cultivation of probiotics: 2 parts by weight of plant lactobacillus lyophilized powder was dissolved in sterile physiological saline and inoculated into a sterilized MRS plate medium, and incubated in a shaking incubator at 37° C. and 160 rpm for 24 h to prepare a seed solution, and then the seed solution was inoculated into an MRS liquid medium at an inoculum volume of 2% (v / v), and the activation was completed after incubation in a shaking incubator at 37° C. and 160 rpm for 48 h.
[0016] Step 5: Preparation of probiotic microcapsules: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix well, and then obtain microcapsules encapsulating probiotics by freeze-drying.
[0017] Preferably, the preparation method of step 1 is as follows: take fresh wet bean dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry bean dregs powder; mix the bean dregs powder with petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain a precipitate and allowed to stand until the petroleum ether is completely volatilized, then add deionized water to the refrigerated defatted bean dregs powder at a ratio of 1:11 (w / w), stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, centrifuge at 7000g, 4°C, 15min and remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse it again, and use 40% The pH value was adjusted to 3.3 with HCl, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 h, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000 g for 15 min, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was redispersed with deionized water at a ratio of 1:5 (w / w), the pH value was adjusted to 7.7, and the mixture was bagged and dialyzed for a total of 72 h, during which the water was changed 5 times. Finally, the mixture was freeze-dried to obtain okara cellulose.
[0018] Preferably, the preparation method of the above step 2 is as follows: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the average particle size of the okara nanocellulose particles is 238nm.
[0019] Preferably, the preparation method of the above step 3 is as follows: under magnetic stirring, the okara nanocellulose and peanut protein are evenly mixed, the mixture is dissolved in distilled water at a mass ratio of 1:10 to deionized water to fully hydrate, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the genipin powder is dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein.
[0020] Application of soybean dregs nanocellulose in the preparation of probiotic microcapsule wall materials.
[0021] Application of genipin in the preparation of probiotic microcapsule wall materials.
[0022] Advantages and effects of the present invention: The present invention fully realizes the high-value utilization of bean dregs, a byproduct of bean product processing, extracts and prepares bean dregs nanocellulose, and uses a natural green new polysaccharide-protein cross-linking agent genipin to prepare a composite product of bean dregs nanocellulose and peanut protein, which is used as a microcapsule wall material to prepare plant lactobacillus microcapsules, realizes the in vivo delivery of plant lactobacillus, and uses plant insoluble polysaccharides as wall materials in the preparation of microcapsules, realizes the utilization of bean dregs, a byproduct of bean product production, protects the intestinal delivery and colonization fermentation biological activity of plant lactobacillus, and better exerts its health benefits. In addition, the present invention is simple to operate, the production raw materials are natural and healthy, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a process flow chart of the present invention.
[0024] Figure 2 It is a curve diagram of the effect of ultrasonic power on the average particle size of okara nanocellulose under the conditions of ultrasonic time of 20 min and ultrasonic temperature of 25° C. in the present invention.
[0025] Figure 3It is a curve diagram of the influence of ultrasonic temperature on the average particle size of okara nanocellulose under the conditions of ultrasonic power of 480w and ultrasonic time of 20min in the present invention.
[0026] Figure 4 It is a curve diagram of the influence of ultrasonic time on the average particle size of okara nanocellulose under the conditions of ultrasonic power of 480w and ultrasonic temperature of 25°C in the present invention.
[0027] Figure 5 Here are the Fourier transform infrared spectra of several products.
[0028] Figure 6 These are scanning electron microscope images of genipin-treated okara nanocellulose and the composite product of genipin-treated okara nanocellulose and peanut protein.
[0029] Figure 7 These are transmission electron micrographs of genipin-treated okara nanocellulose and the composite product of genipin-treated okara nanocellulose and peanut protein.
[0030] Figure 8 It is a simulated diagram of in vitro digestion of free Lactobacillus plantarum, the control group and the microcapsules prepared in Example 1.
[0031] Fig. 9 This is a graph showing the changes in biological activity when heated at 50°C and 68°C for 30 minutes in Test Example 8. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the specific embodiments of the present invention to clearly and completely describe the technical solutions in the specific embodiments of the present invention. Obviously, the specific embodiments described are only part of the specific embodiments of the present invention, not all of the specific embodiments. Based on the specific embodiments of the present invention, all other specific embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The preparation methods in the following embodiments, comparative examples and test examples are conventional methods unless otherwise specified, and the percentage contents are by mass unless otherwise specified.
[0034] Example 1
[0035] A bean dregs nanocellulose probiotic microcapsule, which is composed of a probiotic as a core material and a wall material for embedding the core material; wherein the wall material is composed of bean dregs nanocellulose, peanut protein and genipin, and the probiotic is Lactobacillus plantarum, and is prepared from the following raw materials in parts by weight: 100 parts of bean dregs nanocellulose, 100 parts of peanut protein, 1 part of genipin, and 2 parts of Lactobacillus plantarum. The bean dregs nanocellulose is obtained by physically modifying the raw cellulose extracted from the bean dregs; the peanut protein is food-grade peanut protein; the genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and the Lactobacillus plantarum is a live bacterium after activation and expansion.
[0036] The preparation steps are as follows:
[0037] Step 1: Take fresh wet dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry dregs powder; mix the dregs and petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized to obtain defatted dregs powder for refrigeration, then add deionized water at a ratio of 1:11 (w / w) to the refrigerated defatted dregs powder and stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, then centrifuge at 7000g, 4°C, 15min to remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse the defatted dregs powder again, and use 40% HCl was used to adjust the pH to 3.3, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 hours, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000g for 15 minutes, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was dispersed again with deionized water at a ratio of 1:5 (w / w), the pH was adjusted to 7.7, and the precipitate was bagged and dialyzed for a total of 72 hours, during which the water was changed 5 times, and finally freeze-dried to obtain okara cellulose.
[0038] Step 2: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, and then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the obtained okara nanocellulose particles are uniform and have an average particle size of 238nm; the final yield of okara nanocellulose is 9.65%;
[0039] Step 3: Under magnetic stirring for 12 hours, the weight portions of okara nanocellulose and peanut protein are mixed, the mixture is dissolved in distilled water with deionized water to be fully hydrated, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the weight portions of genipin powder are dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature for 28 hours; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein;
[0040] Step 4: dissolving the plant lactobacillus lyophilized powder by weight in sterile physiological saline, inoculating it into sterilized MRS plate culture medium, culturing it in a shaking table at 37° C. and 160 rpm for 24 h to prepare seed solution, then inoculating the seed solution into MRS liquid culture medium at an inoculum size of 2% (v / v), and culturing it in a shaking table at 37° C. and 160 rpm for 48 h to complete activation;
[0041] Step 5: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix evenly, and then obtain microcapsules encapsulating probiotics by freeze-drying, with an encapsulation rate of 87.65%±1.73%.
[0042] Example 2
[0043] A bean dregs nanocellulose probiotic microcapsule, which is composed of a probiotic as a core material and a wall material for embedding the core material; wherein the wall material is composed of bean dregs nanocellulose, peanut protein and genipin, and the probiotic is Lactobacillus plantarum, and is prepared from the following raw materials in parts by weight: 98 parts of bean dregs nanocellulose, 98 parts of peanut protein, 1.2 parts of genipin, and 2 parts of Lactobacillus plantarum. The bean dregs nanocellulose is obtained by physically modifying the raw cellulose extracted from bean dregs; the peanut protein is food-grade peanut protein; the genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and the Lactobacillus plantarum is a live bacterium after activation and expansion.
[0044] The preparation steps are as follows:
[0045] Step 1: Take fresh wet dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry dregs powder; mix the dregs and petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized to obtain defatted dregs powder for refrigeration, then add deionized water at a ratio of 1:11 (w / w) to the refrigerated defatted dregs powder and stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, then centrifuge at 7000g, 4°C, 15min to remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse the defatted dregs powder again, and use 40% HCl was used to adjust the pH to 3.3, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 hours, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000g for 15 minutes, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was dispersed again with deionized water at a ratio of 1:5 (w / w), the pH was adjusted to 7.7, and the precipitate was bagged and dialyzed for a total of 72 hours, during which the water was changed 5 times, and finally freeze-dried to obtain okara cellulose.
[0046] Step 2: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, and then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the obtained okara nanocellulose particles are uniform and have an average particle size of 238nm; the final yield of okara nanocellulose is 9.65%;
[0047] Step 3: Under magnetic stirring for 12 hours, the weight portions of okara nanocellulose and peanut protein are mixed, the mixture is dissolved in distilled water with deionized water to be fully hydrated, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the weight portions of genipin powder are dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature for 28 hours; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein;
[0048] Step 4: dissolving the plant lactobacillus lyophilized powder by weight in sterile physiological saline, inoculating it into sterilized MRS plate culture medium, culturing it in a shaking table at 37° C. and 160 rpm for 24 h to prepare seed solution, then inoculating the seed solution into MRS liquid culture medium at an inoculum size of 2% (v / v), and culturing it in a shaking table at 37° C. and 160 rpm for 48 h to complete activation;
[0049] Step 5: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix evenly, and then obtain microcapsules encapsulating probiotics by freeze-drying, with an encapsulation rate of 85.15%±1.54%.
[0050] Example 3
[0051] A bean dregs nanocellulose probiotic microcapsule, which is composed of a probiotic as a core material and a wall material for embedding the core material; wherein the wall material is composed of bean dregs nanocellulose, peanut protein and genipin, and the probiotic is Lactobacillus plantarum, and is prepared from the following raw materials in parts by weight: 102 parts of bean dregs nanocellulose, 102 parts of peanut protein, 0.8 parts of genipin, and 2 parts of Lactobacillus plantarum. The bean dregs nanocellulose is obtained by physically modifying the raw cellulose extracted from the bean dregs; the peanut protein is food-grade peanut protein; the genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and the Lactobacillus plantarum is a live bacterium after activation and expansion.
[0052] The preparation steps are as follows:
[0053] Step 1: Take fresh wet dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry dregs powder; mix the dregs and petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized to obtain defatted dregs powder for refrigeration, then add deionized water at a ratio of 1:11 (w / w) to the refrigerated defatted dregs powder and stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, then centrifuge at 7000g, 4°C, 15min to remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse the defatted dregs powder again, and use 40% HCl was used to adjust the pH to 3.3, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 hours, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000g for 15 minutes, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was dispersed again with deionized water at a ratio of 1:5 (w / w), the pH was adjusted to 7.7, and the precipitate was bagged and dialyzed for a total of 72 hours, during which the water was changed 5 times, and finally freeze-dried to obtain okara cellulose.
[0054] Step 2: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, and then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the obtained okara nanocellulose particles are uniform and have an average particle size of 238nm; the final yield of okara nanocellulose is 9.65%;
[0055] Step 3: Under magnetic stirring for 12 hours, the weight portions of okara nanocellulose and peanut protein are mixed, the mixture is dissolved in distilled water with deionized water to be fully hydrated, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the weight portions of genipin powder are dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature for 28 hours; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein;
[0056] Step 4: dissolving the plant lactobacillus lyophilized powder by weight in sterile physiological saline, inoculating it into sterilized MRS plate culture medium, culturing it in a shaking table at 37° C. and 160 rpm for 24 h to prepare seed solution, then inoculating the seed solution into MRS liquid culture medium at an inoculum size of 2% (v / v), and culturing it in a shaking table at 37° C. and 160 rpm for 48 h to complete activation;
[0057] Step 5: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix evenly, and then obtain microcapsules encapsulating probiotics by freeze-drying, with an encapsulation rate of 86.77%±1.79%.
[0058] Example 4
[0059] A bean dregs nanocellulose probiotic microcapsule, which is composed of a probiotic as a core material and a wall material for embedding the core material; wherein the wall material is composed of bean dregs nanocellulose, peanut protein and genipin, and the probiotic is Lactobacillus plantarum, and is prepared from the following raw materials in parts by weight: 101 parts of bean dregs nanocellulose, 99 parts of peanut protein, 1.1 parts of genipin, and 2 parts of Lactobacillus plantarum. The bean dregs nanocellulose is obtained by physically modifying the raw cellulose extracted from bean dregs; the peanut protein is food-grade peanut protein; the genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and the Lactobacillus plantarum is a live bacterium after activation and expansion.
[0060] The preparation steps are as follows:
[0061] Step 1: Take fresh wet dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry dregs powder; mix the dregs and petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized to obtain defatted dregs powder for refrigeration, then add deionized water at a ratio of 1:11 (w / w) to the refrigerated defatted dregs powder and stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, then centrifuge at 7000g, 4°C, 15min to remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse the defatted dregs powder again, and use 40% HCl was used to adjust the pH to 3.3, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 hours, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000g for 15 minutes, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was dispersed again with deionized water at a ratio of 1:5 (w / w), the pH was adjusted to 7.7, and the precipitate was bagged and dialyzed for a total of 72 hours, during which the water was changed 5 times, and finally freeze-dried to obtain okara cellulose.
[0062] Step 2: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, and then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the obtained okara nanocellulose particles are uniform and have an average particle size of 238nm; the final yield of okara nanocellulose is 9.65%;
[0063] Step 3: Under magnetic stirring for 12 hours, the weight portions of okara nanocellulose and peanut protein are mixed, the mixture is dissolved in distilled water with deionized water to be fully hydrated, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the weight portions of genipin powder are dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature for 28 hours; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein;
[0064] Step 4: dissolving the plant lactobacillus lyophilized powder by weight in sterile physiological saline, inoculating it into sterilized MRS plate culture medium, culturing it in a shaking table at 37° C. and 160 rpm for 24 h to prepare seed solution, then inoculating the seed solution into MRS liquid culture medium at an inoculum size of 2% (v / v), and culturing it in a shaking table at 37° C. and 160 rpm for 48 h to complete activation;
[0065] Step 5: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix evenly, and then obtain microcapsules encapsulating probiotics by freeze-drying, with an encapsulation rate of 84.51%±1.82%.
[0066] Example 5
[0067] A bean dregs nanocellulose probiotic microcapsule, which is composed of a probiotic as a core material and a wall material for embedding the core material; wherein the wall material is composed of bean dregs nanocellulose, peanut protein and genipin, and the probiotic is Lactobacillus plantarum, and is prepared from the following raw materials in the stated weight proportions: 99 parts of bean dregs nanocellulose, 101 parts of peanut protein, 0.9 parts of genipin, and 2 parts of Lactobacillus plantarum. The bean dregs nanocellulose is obtained by physically modifying the raw cellulose extracted from bean dregs; the peanut protein is food-grade peanut protein; the genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and the Lactobacillus plantarum is a live bacterium after activation and expansion.
[0068] The preparation steps are as follows:
[0069] Step 1: Take fresh wet dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry dregs powder; mix the dregs and petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized to obtain defatted dregs powder for refrigeration, then add deionized water at a ratio of 1:11 (w / w) to the refrigerated defatted dregs powder and stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, then centrifuge at 7000g, 4°C, 15min to remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse the defatted dregs powder again, and use 40% HCl was used to adjust the pH to 3.3, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 hours, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000g for 15 minutes, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was dispersed again with deionized water at a ratio of 1:5 (w / w), the pH was adjusted to 7.7, and the precipitate was bagged and dialyzed for a total of 72 hours, during which the water was changed 5 times, and finally freeze-dried to obtain okara cellulose.
[0070] Step 2: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, and then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the obtained okara nanocellulose particles are uniform and have an average particle size of 238nm; the final yield of okara nanocellulose is 9.65%;
[0071] Step 3: Under magnetic stirring for 12 hours, the weight portions of okara nanocellulose and peanut protein are mixed, the mixture is dissolved in distilled water with deionized water to be fully hydrated, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the weight portions of genipin powder are dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature for 28 hours; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein;
[0072] Step 4: dissolving the plant lactobacillus lyophilized powder by weight in sterile physiological saline, inoculating it into sterilized MRS plate culture medium, culturing it in a shaking table at 37° C. and 160 rpm for 24 h to prepare seed solution, then inoculating the seed solution into MRS liquid culture medium at an inoculum size of 2% (v / v), and culturing it in a shaking table at 37° C. and 160 rpm for 48 h to complete activation;
[0073] Step 5: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix evenly, and then obtain microcapsules encapsulating probiotics by freeze-drying, with an encapsulation rate of 86.13%±1.65%.
[0074] Example 6
[0075] A bean dregs nanocellulose probiotic microcapsule, which is composed of a probiotic as a core material and a wall material for embedding the core material; wherein the wall material is composed of bean dregs nanocellulose, peanut protein and genipin, and the probiotic is Lactobacillus plantarum, and is prepared from the following raw materials in the stated weight proportions: 99.5 parts of bean dregs nanocellulose, 99.5 parts of peanut protein, 0.95 parts of genipin, and 2 parts of Lactobacillus plantarum. The bean dregs nanocellulose is obtained by physically modifying the raw cellulose extracted from bean dregs; the peanut protein is food-grade peanut protein; the genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and the Lactobacillus plantarum is a live bacterium after activation and expansion.
[0076] The preparation steps are as follows:
[0077] Step 1: Take fresh wet dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry dregs powder; mix the dregs and petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized to obtain defatted dregs powder for refrigeration, then add deionized water at a ratio of 1:11 (w / w) to the refrigerated defatted dregs powder and stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, then centrifuge at 7000g, 4°C, 15min to remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse the defatted dregs powder again, and use 40% HCl was used to adjust the pH to 3.3, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 hours, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000g for 15 minutes, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was dispersed again with deionized water at a ratio of 1:5 (w / w), the pH was adjusted to 7.7, and the precipitate was bagged and dialyzed for a total of 72 hours, during which the water was changed 5 times, and finally freeze-dried to obtain okara cellulose.
[0078] Step 2: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, and then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the obtained okara nanocellulose particles are uniform and have an average particle size of 238nm; the final yield of okara nanocellulose is 9.65%;
[0079] Step 3: Under magnetic stirring for 12 hours, the weight portions of okara nanocellulose and peanut protein are mixed, the mixture is dissolved in distilled water with deionized water to be fully hydrated, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the weight portions of genipin powder are dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature for 28 hours; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein;
[0080] Step 4: dissolving the plant lactobacillus lyophilized powder by weight in sterile physiological saline, inoculating it into sterilized MRS plate culture medium, culturing it in a shaking table at 37° C. and 160 rpm for 24 h to prepare seed solution, then inoculating the seed solution into MRS liquid culture medium at an inoculum size of 2% (v / v), and culturing it in a shaking table at 37° C. and 160 rpm for 48 h to complete activation;
[0081] Step 5: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix evenly, and then obtain microcapsules encapsulating probiotics by freeze-drying, with an encapsulation rate of 86.99%±1.57%.
[0082] Example 7
[0083] A bean dregs nanocellulose probiotic microcapsule, which is composed of a probiotic as a core material and a wall material for embedding the core material; wherein the wall material is composed of bean dregs nanocellulose, peanut protein and genipin, and the probiotic is Lactobacillus plantarum, and is prepared from the following raw materials in parts by weight: 100.5 parts of bean dregs nanocellulose, 99.5 parts of peanut protein, 1.05 parts of genipin, and 2 parts of Lactobacillus plantarum. The bean dregs nanocellulose is obtained by physically modifying the raw cellulose extracted from bean dregs; the peanut protein is food-grade peanut protein; the genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and the Lactobacillus plantarum is a live bacterium after activation and expansion.
[0084] The preparation steps are as follows:
[0085] Step 1: Take fresh wet dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry dregs powder; mix the dregs and petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized to obtain defatted dregs powder for refrigeration, then add deionized water at a ratio of 1:11 (w / w) to the refrigerated defatted dregs powder and stir and mix, use 1M sodium hydroxide solution to adjust pH=9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, then centrifuge at 7000g, 4°C, 15min to remove the residue, add deionized water at a ratio of 1:4 (w / w) to disperse the defatted dregs powder again, and use 40% HCl was used to adjust the pH to 3.3, and the mixture was stirred and dispersed again. After being treated in a high-pressure steam sterilizer at 120°C for 2 hours, a liquid with complete protein removal was obtained. After cooling to room temperature, the mixture was centrifuged at 7000g for 15 minutes, and the precipitate was washed with deionized water to remove the residual water-soluble polysaccharides. The wet precipitate was dispersed again with deionized water at a ratio of 1:5 (w / w), the pH was adjusted to 7.7, and the precipitate was bagged and dialyzed for a total of 72 hours, during which the water was changed 5 times, and finally freeze-dried to obtain okara cellulose.
[0086] Step 2: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, and then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the obtained okara nanocellulose particles are uniform and have an average particle size of 238nm; the final yield of okara nanocellulose is 9.65%;
[0087] Step 3: Under magnetic stirring for 12 hours, the weight portions of okara nanocellulose and peanut protein are mixed, the mixture is dissolved in distilled water with deionized water to be fully hydrated, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and the weight portions of genipin powder are dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature for 28 hours; then 95% v / v ethanol is added to the reaction solution, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein;
[0088] Step 4: dissolving the plant lactobacillus lyophilized powder by weight in sterile physiological saline, inoculating it into sterilized MRS plate culture medium, culturing it in a shaking table at 37° C. and 160 rpm for 24 h to prepare seed solution, then inoculating the seed solution into MRS liquid culture medium at an inoculum size of 2% (v / v), and culturing it in a shaking table at 37° C. and 160 rpm for 48 h to complete activation;
[0089] Step 5: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix evenly, and then obtain microcapsules encapsulating probiotics by freeze-drying, with an encapsulation rate of 85.39±1.74%.
[0090] Comparative Example 1
[0091] In Example 1, the ratio of soybean dregs nanocellulose: peanut protein: genipin is 90:110:1.2, and the rest is the same as in Example 1. The embedding rate is 67.78%±1.52%.
[0092] Comparative Example 2
[0093] In Example 1, the ratio of soybean dregs nanocellulose: peanut protein: genipin is 90:120:1, and the rest is the same as in Example 1. The embedding rate is 70.85%±1.63%.
[0094] Comparative Example 3
[0095] In Example 1, the ratio of soybean dregs nanocellulose: peanut protein: genipin is 115:80:1, and the rest is the same as in Example 1. The embedding rate is 64.37±1.79%.
[0096] Comparative Example 4
[0097] The cross-linking agent genipin in Example 1 was replaced by gelatin, and the rest was the same as Example 1. The embedding rate was 47.56%±1.58%.
[0098] Comparative Example 5
[0099] The cross-linking agent genipin in Example 1 was replaced by carbodiimide, and the rest was the same as Example 1. The embedding rate was 44.19%±1.61%.
[0100] Comparative Example 6
[0101] The cross-linking agent genipin in Example 1 was replaced by a phosphate group, and the rest was the same as Example 1. The embedding rate was 45.33%±1.75%.
[0102] Comparative Example 7
[0103] The cross-linking agent genipin in Example 1 was replaced by boric acid, and the rest was the same as Example 1. The embedding rate was 42.89%±1.67%.
[0104] Comparative Example 8
[0105] The cross-linking agent genipin in Example 1 was replaced by acrylamide, and the rest was the same as Example 1. The embedding rate was 46.39%±1.53%.
[0106] Comparison of Example 1 and Comparative Examples 4-8 shows that the use of genipin can better cause the mixed solution of soybean dregs nanocellulose and peanut protein to undergo cross-linking reaction. In view of the advantages of wide availability, simple preparation and high safety of polysaccharide-based stabilizers, most of them are biomacromolecules formed based on glucose structural units, and the rich hydroxyl groups on the surface lead to their high hydrophilicity. High hydrophilicity will inevitably lead to a decrease in emulsification performance, limiting their practical application in certain aspects. The cross-linking reaction of genipin with the mixed solution of soybean dregs nanocellulose and peanut protein can significantly improve the hydrophobicity of its individual fibers and enhance the emulsification performance.
[0107] The present invention is further verified by test examples below.
[0108] Test Example 1
[0109] In step 2 of Example 1, under the conditions of ultrasonic time of 20 min and ultrasonic temperature of 25° C., different ultrasonic powers were used to treat the okara nanocellulose, and the other preparation steps remained unchanged, such as Figure 2 As shown in the figure, it can be seen that as the ultrasonic power gradually increases from 320w to 480w, the okara nanocellulose obtains a smaller particle size, because the higher ultrasonic frequency can better destroy the structure of the okara raw cellulose particles and promote the fracture of the cellulose skeleton. At 480w, the average particle size of the okara nanocellulose can reach about 265nm. As the ultrasonic power gradually increases, the average particle size gradually increases, because the excessively high ultrasonic power affects the viscosity of the okara cellulose pulp.
[0110] Test Example 2
[0111] In step 2 of Example 1, under the conditions of ultrasonic power of 480W and ultrasonic time of 20min, different ultrasonic temperatures were used to treat the okara nanocellulose, and the other preparation steps remained unchanged, such as Figure 3 As shown in the figure, it can be seen that the average particle size of okara nanocellulose does not change much, and the test results fluctuate between 266-283nm. This is because under the same treatment time and treatment frequency, the five levels of ultrasonic temperature have no significant effect on the mechanical force on the okara cellulose pulp during ultrasonic treatment, and a higher room temperature may better promote the depolymerization and repolymerization of the carbohydrate chains of the cellulose polymer.
[0112] Test Example 3
[0113] In step 2 of Example 1, under the conditions of ultrasonic power of 480w and ultrasonic temperature of 25°C, the okara nanocellulose was treated with different ultrasonic times, and the other preparation steps remained unchanged, such as Figure 4 As shown, it can be seen that the decrease in the average particle size of cellulose shows a positive correlation with the increase in ultrasonic time. When the ultrasonic time reaches 30 minutes, okara nanocellulose with an average particle size of 238nm can be obtained. This is because as the ultrasonic time increases, the okara cellulose is evenly dispersed in the deionized water, the system liquid is fully sheared and may change the cohesion and viscosity; and long-term ultrasonic treatment will also increase the temperature of the system liquid, promote the breakage of cellulose, and obtain fine okara nanocellulose.
[0114] An orthogonal test was conducted to obtain the best conditions for preparing okara nanocellulose in the single-factor experiment. The three-factor three-level orthogonal analysis method was used to explore the effects of ultrasonic power, ultrasonic time, and ultrasonic temperature on the average particle size of okara nanocellulose, so as to determine the optimal conditions for nano-sizing okara raw cellulose, as shown in Tables 1 and 2.
[0115] Table 1 Factor levels of orthogonal experiment for optimizing preparation of okara nanocellulose
[0116] level Ultrasonic power Ultrasound time Ultrasonic temperature 1 400 15 20 2 480 20 25 3 560 25 30
[0117] Table 2 Orthogonal experiment results
[0118] serial number Ultrasonic power Ultrasound time Ultrasonic temperature Average particle size (nm) Group 1 400W 15min 20℃ 309±13 Group 2 400W 20min 30℃ 304±4 Group 3 400W 25min 25℃ 298±19 Group 4 480W 15min 30℃ 287±5 Group 5 480W 20min 25℃ 262±9 Group 6 480W 25min 20℃ 255±7 Group 7 560W 15min 25℃ 279±13 Group 8 560W 20min 20℃ 264±19 Group 9 560W 25min 30℃ 276±4 Group K1 911 875 828 Group K2 804 830 839 Group K3 819 829 867 Group k1 303.67 291.67 276.00 Group k2 268.00 276.67 279.67 Group k3 273.00 276.33 289.00 R 35.67 15.34 13 Optimal level A2 B3 C1
[0119] As shown in Table 1 and Table 2, the order of the range R is (A) ultrasonic power > (B) ultrasonic time > (C) ultrasonic temperature. It can be concluded that the factor that has the greatest impact on the average particle size of okara nanocellulose is ultrasonic power, and the combination of A2, B3, and C1 is the best preparation condition. Under this condition, the average particle size of okara nanocellulose obtained is 255nm, which is a good test result. Therefore, in the subsequent preparation of okara nanocellulose, the combination of A2, B3, and C1 is used, and the average particle size of okara nanocellulose is used as the evaluation index. At this time, the best process parameters are ultrasonic power 480w, ultrasonic time 25min, and ultrasonic temperature 20℃.
[0120] The conclusion is as follows:
[0121] In the single-factor experiment, at the same ultrasonic time and ultrasonic temperature, an ultrasonic power of 480w provided the smallest size of okara nanocellulose. The change of ultrasonic power affected the skeleton fracture of okara raw cellulose and the viscosity of okara cellulose pulp, thereby affecting the average particle size of okara nanocellulose. When the ultrasonic time and ultrasonic power were fixed, the effect of ultrasonic temperature on the average particle size was relatively small, and the change of okara cellulose pulp temperature would affect the depolymerization and polymerization of carbohydrate chains. When the ultrasonic time was used as a variable, the average particle size of okara nanocellulose gradually decreased with the increase of ultrasonic time.
[0122] Orthogonal test can reflect the order of the influence of various factors on the average particle size of okara nanocellulose. The most important factor is ultrasonic power, followed by ultrasonic time, and then ultrasonic temperature. If the okara nanocellulose after high-pressure homogenization at 10000rpm and 5min is mechanically treated under the process conditions of ultrasonic power 480w, ultrasonic time 25min, and ultrasonic temperature 20℃, the particle size of okara cellulose can be reduced to 255nm, which is a successful nano-treatment of okara cellulose.
[0123] The yield of okara nanocellulose was calculated. After the fresh wet okara was dried to constant weight, it was subjected to a series of treatments at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20℃, and then freeze-dried to recover the okara nanocellulose, with a final yield of about 9.65%.
[0124] Test Example 4
[0125] The peanut protein treated with jingpinnib alone in step 3 of Example 1 is recorded as product A; the soybean dregs nanocellulose treated with jingpinnib alone is recorded as product B.
[0126] like Figure 5 As shown in the figure, the amide I band (C=O stretching) and amide II band (NH bending and CN stretching) of the proteins of the four products of okara nanocellulose-peanut protein cross-linked product, okara nanocellulose-genipin product, peanut protein and okara nanocellulose are at 1650 cm-1, respectively. -1 and 1540cm -1 There is a characteristic absorption near the wavelength of carbohydrates, which is mainly concentrated at 1180-953 cm -1 In the spectrum of soybean okara nanocellulose-peanut protein cross-linked products, the 3500 and 3000 cm -1 The peaks in the range 3000–3700 cm are OH stretching vibrations indicating intermolecular and intramolecular hydrogen bonds. -1 The broad tension peak near 2925cm is attributed to the OH stretching of hydrogen bonds, mainly from the polysaccharides in okara, especially okara nanocellulose and hemicellulose.-1 The peaks near the C-H stretching bands of the polysaccharide methylene groups are 1635 cm -1 and 1408cm -1 The C-OO asymmetric and symmetric stretching is typical of galacturonic acid, 1260 and 1100 cm -1 is the stretching vibration of the CO group, especially associated with the glycosidic bond (COC), 1400 cm -1 The CN stretching vibration at also indicated that the mixture of okara nanocellulose and peanut protein had a higher number density after cross-linking with genipin.
[0127] The wavelength around 890 cm was observed in all four samples. -1 The small infrared peak at 1735 cm-1 reflects the prevalence of β-glycosidic bonds. -1 Another smaller infrared peak nearby is the vibration of the ester bond of the carboxyl group in lignin and hemicellulose, and the vibration of the acetyl and uronic acid ester groups of hemicellulose. -1 The characteristic peak of C=C bond appears at 1544 cm-1, while the characteristic peaks of amide I and amide II of cellulose-protein cross-linked products are slightly offset, which can be seen at 1544 cm-1. -1 The amide II band is identified at 1635 cm, which is characteristic of NH deformation and can be attributed to the formation of secondary amide as a result of the reaction between genipin ester and hydroxyl group and the Cht amino group. -1 The peak at can be attributed to the C=O stretching in the secondary amide. This suggests the changes in functional groups brought about by the genipin crosslinker, such as the carbonylamine bond formed by the carbonylamine condensation reaction, the C=O bond of the Amadori product, the C=N bond of the Schiff base, the CN bond of the pyrazine and other covalent bonds between the polysaccharide molecule and the protein molecule. In summary, the spectrum of the crosslinked product not only suggests that the functional groups of the polysaccharide and the protein have changed, but also obtains the characteristic absorption peaks of cellulose and protein, which proves that the crosslinked product retains some structural characteristics of the polysaccharide and the protein, and thus can retain the functional characteristics of the two compounds, such as gel properties / emulsification properties / mechanical properties, etc., and at the same time confirms the occurrence of glycosylation crosslinking reaction.
[0128] Test Example 5
[0129] The control group was obtained by treating the okara nanocellulose with genipin alone in step 3 of Example 1. The control group of Experimental Example 5 and the cross-linked product in Example 1 were subjected to scanning electron microscopy and transmission electron microscopy.
[0130] like Figure 6 As shown, Figure 6The ac in the figure is the control group, and nano-level cellulose is observed. The original structure of the okara cellulose is destroyed after the combined treatment of ultrasound and homogenization. The strong shear force, cavitation force and turbulent force in the mechanical process cause the particle size of the okara cellulose to decrease and release the okara nanocellulose. Figure 6 DF in the figure is the cross-linked product. After the okara nanocellulose was cross-linked with genipin and peanut protein, the cross-linked products showed different morphologies. The okara nanocellulose treated alone had an irregular fiber structure and a smooth surface, and showed a loose and porous structure. The cross-linked product sample contained relatively large and aggregated particles. Compared with genipin, the okara nanocellulose treated alone showed a tighter structure without visible pores. The more stress weak points in the wall material structure, the more obvious the homogenization effect. This porosity difference will affect the embedding effect of plant lactobacillus microencapsulation and the release of probiotics from the microcapsule. The change in the microstructure of the cross-linked product is because the cross-linking of okara nanocellulose and peanut protein leads to an increase in molecular weight and molecular particle size, and the chemical bonds between okara nanocellulose molecules are destroyed and new carbonylamine bonds are formed with peanut protein, completing the dehydration condensation glycosylation grafting reaction.
[0131] like Figure 7 As shown, Figure 7 Figures a and b are transmission electron microscope images of okara nanocellulose treated with genipin alone. Figure 7 The images of the cross-linked products are shown in Figures cd and cd. It was observed that the control group of okara nanocellulose consisted of two types of nanofibers, thick and thin. Some of the thin nanofibers were entangled with each other to form thick nanofibers, and some nanofiber clumps were formed between them. The cross-linked products showed more ordered and fine nanofiber particles, and the dissociation of entangled or clustered nanofibers was promoted in the cross-linking reaction.
[0132] Test Example 6
[0133] Four samples of okara nanocellulose, genipin-okara nanocellulose, genipin-okara nanocellulose-peanut protein and genipin-peanut protein were taken for emulsification capacity determination, as shown in the following table:
[0134] Sample name <![CDATA[EAI(m 2 / g)]]> ESI(min) Okara Nanocellulose 11.92±0.83 15.28±0.84 Genipin-soybean dregs nanocellulose 18.36±1.09 16.31±0.88 Genipin-Okara Nanocellulose-Peanut Protein 20.63±1.36 18.77±1.00 Genipin-Peanut Protein 19.43±0.90 18.42±1.03
[0135] The emulsification activity index and emulsification stability index of the cross-linked product were 20.635m 2 / g and 18.768. The larger the EAI or ESI, the better its emulsification performance or emulsion stability. As shown in the table, compared with untreated or single-treated okara nanocellulose, the ability of the cross-linked product to form and stabilize the emulsion is improved. The poor emulsification performance of untreated okara is related to its uneven dispersion in water. The grafting reaction of macromolecular cellulose and protein changes the interfacial adsorption, penetration and even interfacial structural rearrangement of the molecules. The cross-linked product can more effectively stabilize the emulsion due to higher water dispersibility or colloidal stability. After cross-linking treatment, more hydrophobic parts are exposed to the molecular surface of the cross-linked product, or the dissolution of protein into the aqueous phase may be conducive to the formation of finer emulsions. The emulsification performance of the cross-linked product is also related to its particle size. At the same solid concentration, small-sized particles will have more area to contact with the interfacial area of the droplets, thereby showing a higher efficiency in stabilizing the emulsion.
[0136] Test Example 7
[0137] In vitro digestion simulation experiment of bean curd nanocellulose probiotic microcapsules prepared in Example 1 was carried out using conventional methods in the art. The experimental results are as follows:
[0138] like Figure 8 As shown in the figure, the activity of free Lactobacillus plantarum dropped sharply within 0-2h, from 11.32logCFU·mL -1 Reduced to 7.31logCFU·mL -1 The bioactivity loss of the microcapsules in the control group was slightly slower within 0-4h, and the activity of the cross-linked products changed from 11.12log CFU·mL -1 Reduced to 9.27log CFU·mL -1 , after 4 h of simulation, it decreased to 7.62 logCFU·mL -1 The cross-linked composite structure of genipin enhances the buffering capacity of the wall material and can form a dense network structure during the microencapsulation process, which is conducive to enhancing the steric hindrance effect and can effectively slow down the diffusion of digestive juice in the microcapsules, thereby reducing the probability of contact between Lactobacillus plantarum and acid, digestive enzymes, bile salts, etc., and effectively improving the survival rate of Lactobacillus plantarum. The change range of the number of free live bacteria of Lactobacillus plantarum reached an inflection point at 6 hours, and the biological activity at this time was only 4.29logCFU·mL -1 , which is lower than the minimum concentration of 6log CFU·mL that can exert health benefits in the human body -1This confirms the importance of using microencapsulation technology to protect Lactobacillus plantarum in artificial gastric juice. The decline curves of the biological activity of the two groups of microcapsules reached inflection points at 4h and 6h, respectively, which is related to the different acid resistance of the two wall materials. In the SGF digestion stage, pepsin caused different degrees of damage to the outer walls of the two microcapsules, while in the subsequent SIF digestion stage, the pH in the environment increased and the inactivation degree of Lactobacillus plantarum gradually decreased.
[0139] Test Example 8
[0140] Study on thermal stability of soybean dregs nanocellulose probiotic microcapsules prepared in Example 1
[0141] Test method: 0.5 g of microcapsules prepared by the method of Example 1 (cross-linked product) and Comparative Example 5 (control product) were respectively precipitated in 5 mL of sterile saline. Fig. 9 As shown, the samples were heated in a water bath at 50°C and 68°C for 10 min, 20 min and 30 min, respectively, then taken out immediately, rapidly cooled to room temperature in an ice bath, and then the viable bacteria were counted.
[0142] The probiotic microcapsules prepared from the cross-linked product of the present invention have a biological activity of 8.35 log CFU·mL after being heated at 50°C for 30 min. -1 , providing effective protection for the activity of Lactobacillus plantarum, while the microcapsules prepared from the control product had a biological activity of 6.52 log CFU·mL at the end of heating. -1 The difference in thermal stability of microcapsules of the two products may be caused by the difference in thermal stability of the wall material or the difference in the structure of the physical barrier formed for the microcapsules. Different structures will affect the embedding effect of the wall material on the core material and the degree and rate of diffusion of external heat into the microcapsules.
[0143] When the heating temperature is 68℃, -1 The number of free Lactobacillus plantarum viable bacteria at 0 min showed the largest drop, and after 30 min, the number of viable bacteria increased from 11.32 log CFU mL -1 Significantly reduced to 3.72log CFU·mL -1 The probiotic microcapsules of the cross-linked product of the present invention can still maintain 7.59 log CFU·mL after heating for 30 minutes. -1 This indicates that the cross-linked probiotic microcapsules of the present invention can still exert their health benefits after being processed under pasteurization conditions commonly used in the food industry, while the viable bacterial count of the control product microcapsules heated at 68°C for 30 min was 5.56 log CFU·mL -1Therefore, the test results of the control product and the cross-linked product of the present invention under pasteurization conditions show that the cross-linked product of the present invention will play a better protective role as a wall material.
[0144] Test Example 9
[0145] Study on the mechanical stability of soybean dregs nanocellulose probiotic microcapsules prepared in Example 1
[0146] 0.5 g of microcapsules prepared by the method of Example 1 (cross-linked product) and the method of Comparative Example 6 (control product) were respectively precipitated in 5 mL of sterile physiological saline, centrifuged at 4 ° C and 12000 g for 20 min, and then the viable bacteria were counted. The microcapsules were treated under the centrifugal condition of 12000 g to explore the effect of centrifugal force on the biological activity of free Lactobacillus plantarum and its microcapsules. The results showed that the free Lactobacillus plantarum and the microcapsules embedded with two wall materials were treated separately at 4 ° C. The activity of free Lactobacillus plantarum increased from the initial 11.32 log CFU·mL -1 Reduced to 8.91log CFU·mL -1 The biological activity of the probiotic microcapsules prepared by the cross-linked product increased from 11.12 log CFU·mL -1 Reduced to 10.08log CFU·mL -1 The probiotic activity of the control product increased from 11.06 log CFU·mL -1 Change to 9.63log CFU·mL -1 The test results show that both microcapsule wall materials show effective protection effect on Lactobacillus plantarum, and the proportion of live bacteria retained by the cross-linked product of the present invention reflects that it can provide better mechanical stability as a wall material.
[0147] Test Example 10
[0148] Study on the storage stability of soybean dregs nanocellulose probiotic microcapsules prepared in Example 1
[0149] The original bacterial suspension and the probiotic microcapsules prepared using the wall material of Example 1 (cross-linked product) and the wall material of Test Example 4 (control product) were freeze-dried respectively to prepare 3 groups of freeze-dried powders, which were then placed in sterile centrifuge tubes and stored in a dryer at room temperature (25°C) for 30 days. Samples were taken and counted at 0d, 10d, 20d, and 30d. The specific sampling and counting method was as follows: the probiotic microcapsules and plant lactobacillus powder were evenly dispersed in sterile physiological saline at a ratio of 1:100 (w%:v%). Live bacteria count.
[0150] During storage at room temperature, the number of free and microencapsulated Lactobacillus plantarum viable bacteria decreased over time. After 10 days of storage at room temperature, the number of free viable bacteria decreased from 11.32 log CFU·mL -1 Reduced to 8.48log CFU·mL -1 The microcapsules embedded with the cross-linked product of the present invention still maintained 10.35 log CFU·mL -1 The biological activity of the control product was detected at 9.58 log CFU·mL -1 However, with the extension of storage time, the biological activity of the probiotic microcapsules embedded in the two wall materials gradually decreased. After storage at room temperature for 20 days, the cross-linked microcapsules of the present invention retained 9.51logCFU·mL -1 The biological activity of Lactobacillus plantarum decreased to 6.32 log CFU·mL. -1 This trend intensified with the extension of storage time. When the storage time reached 30 days, only 5.47±0.34 log CFU·mL of free Lactobacillus plantarum remained. -1 The number of live bacteria in the cross-linked product plant lactobacillus microcapsules of the present invention increased from 11.12 log CFU·mL at the beginning of storage. -1 Reduced to 8.40 log CFU·mL -1 , while the biological activity of the probiotic microcapsules prepared by the control product was 6.80log CFU·mL -1 The test results show that the storage stability of the present invention is better at room temperature.
[0151] The above embodiments and test examples show the application of okara nanocellulose and genipin in the preparation of probiotic microcapsule wall materials.
Claims
1. A soybean dregs nanocellulose probiotic microcapsule, characterized in that It consists of a core material with probiotics as the core material and a wall material that embeds the core material; the wall material is composed of soybean dregs nanocellulose, peanut protein and genipin, and the probiotics are plant lactobacillus.
2. The soybean dregs nanocellulose probiotic microcapsule according to claim 1, characterized in that it is prepared from the following raw materials in the stated weight proportions: 98-102 parts of soybean dregs nanocellulose, 98-102 parts of peanut protein, 0.8-1.2 parts of genipin, and 2 parts of Lactobacillus plantarum.
3. The soybean dregs nanocellulose probiotic microcapsule according to claim 2, characterized in that it is prepared from the following raw materials in the stated weight proportions: 100 parts of soybean dregs nanocellulose, 100 parts of peanut protein, 1 part of genipin, and 2 parts of Lactobacillus plantarum.
4. The soybean dregs nanocellulose probiotic microcapsule according to claim 1, 2 or 3, characterized in that Bean dregs nanocellulose is obtained by physically modifying the original cellulose extracted from bean dregs; peanut protein is food grade peanut protein; genipin is a natural polysaccharide-protein complex cross-linking reagent extracted from Gardenia jasminoides; and Lactobacillus plantarum is a live bacterium after activation and expansion.
5. A method for preparing soybean dregs nanocellulose probiotic microcapsules, characterized in that Here are the steps: Step 1: Extraction of okara cellulose: Fresh okara is dried, defatted, deproteinized, water-soluble polysaccharides are removed, dialyzed and purified, and then recovered and freeze-dried to obtain okara cellulose; Step 2: Preparation of okara nanocellulose: treating the okara raw cellulose with ultrasound and homogenization to obtain physically modified okara nanocellulose; Step 3: Preparation of a composite product of okara nanocellulose and peanut protein: 98-102 parts by weight of okara nanocellulose and 98-102 parts by weight of Zhonglian peanut protein are used to prepare a composite product with 0.8-1.2 parts by weight of genipin as a cross-linking agent to obtain a wall material for embedding probiotics; Step 4: Activation and cultivation of probiotics: Dissolve 2 parts by weight of plant lactobacillus freeze-dried powder in sterile physiological saline and inoculate into sterilized MRS plate culture medium, incubate in a shaker at 37°C and 160 rpm for 24 hours to prepare seed solution, then inoculate the seed solution into MRS liquid culture medium at an inoculum rate of 2% (v / v), and incubate in a shaker at 37°C and 160 rpm for 48 hours to complete activation; Step 5: Preparation of probiotic microcapsules: Take the activated probiotic suspension and centrifuge it at 4°C and 2500r / min for 10min, collect the precipitate, and disperse the precipitate in physiological saline to obtain a suspension, mix the suspension with the wall material, use a homogenizer at 12000g for 2min, mix well, and then obtain microcapsules encapsulating probiotics by freeze-drying.
6. The method for preparing okara nanocellulose probiotic microcapsules according to claim 5, characterized in that The preparation method of step 1 is as follows: take fresh wet bean dregs and dry them at 65°C for 10 hours to constant weight and grind and sieve to obtain dry bean dregs powder; mix the bean dregs powder with petroleum ether at a solid-liquid ratio of 1:15 (g / mL), stir and defatted for 6 hours, defatted twice under the above conditions, centrifuged to obtain the precipitate and let it stand until the petroleum ether is completely volatilized, then add deionized water to the refrigerated defatted bean dregs powder at a ratio of 1:11 (w / w), stir and mix, use 1M sodium hydroxide solution to adjust the pH to 9.3, then place it in a 62°C water bath for 50 minutes, keep stirring at 500 rpm, centrifuge and remove the residue at 7000g, 4°C, 15min, add deionized water at a ratio of 1:4 (w / w) to disperse it again, and use 40% Adjust the pH value to 3.3 with HCl, stir and disperse it again, and treat it in a high-pressure steam sterilizer at 120℃ for 2h to obtain a deproteinized liquid; cool it to room temperature and centrifuge it at 7000g for 15min to take out the precipitate and wash away the residual water-soluble polysaccharides with deionized water; the wet precipitate is redispersed with deionized water at a ratio of 1:5 (w / w), adjust the pH value to 7.7, and bag it for dialyze for a total of 72h, during which the water is changed 5 times, and finally freeze-dried to obtain okara cellulose.
7. The method for preparing okara nanocellulose probiotic microcapsules according to claim 5, characterized in that The preparation method of step 2 is as follows: fully disperse the okara raw cellulose in deionized water, homogenize at 10,000 rpm for 5 minutes at 24°C, then treat it at an ultrasonic power of 480w, an ultrasonic time of 25min, and an ultrasonic temperature of 20°C, and then dry it at -65°C with a vacuum freeze dryer until a constant weight is reached to obtain okara nanocellulose; the average particle size of the okara nanocellulose particles is 232-325nm.
8. The method for preparing soybean dregs nanocellulose probiotic microcapsules according to claim 5, characterized in that The preparation method of step 3 is as follows: under magnetic stirring, the okara nanocellulose and peanut protein are evenly mixed, the mixture is dissolved in distilled water at a mass ratio of 1:10 to deionized water to fully hydrate, and then the pH is adjusted to 7.7 with 0.1 mol / L NaOH solution and 0.1 mol / L HCl solution, and genipin powder is dispersed in the prepared mixed solution to induce a cross-linking reaction, and magnetic stirring is performed at room temperature; 95% v / v ethanol is added to the reaction solution to terminate the cross-linking reaction, and after standing at room temperature for 3 hours, the precipitate is collected by centrifugation at 8000g for 15 minutes, washed with 75% v / v ethanol, and then freeze-dried and recovered to obtain a composite product of okara nanocellulose and peanut protein.
9. Use of the soybean dregs nanocellulose according to claims 1-8 in preparing probiotic microcapsule wall materials.
10. Use of genipin according to claims 1-8 in preparing probiotic microcapsule wall materials.